EVALUASI PROGRAM ARPISAN ROSAKTI SEBAGAI STRATEGI MBS MELALUI MODEL CONTEXT, INPUT, PROCESS, PRODUCT - Alifiya Sabilla Ramadhani; Aulia Arista Afiarni; Alisha Salma Salsabila; Aflah Dimas Dewanga; Aksyarul Khairy; Raden Bambang Sumarsono; Wildan Darma Setiawan (Jurnal Manajemen Pendidikan, 2026)
This study aims to evaluate the Arsipan Rosakti program (Pisangcandi Sadar, Aktif, Kreatif, Terapkan IT) as strategy for implementing School Based Management (SBM) at SDN PISANGCANDI 2 using the CIPP (Context, Input, Process, Product) evaluation model. This evaluation was conducted to obtain a comprehensive picture of the program's suitability to school needs, resource readiness, implementation process and the program’s impact on educational quality. This study used a qualitative approach with a case study type. Research subjects included the principal and public relations staff. Data collection techniques were carried out through interviews and documentation. Data analysis was carried out based on the four components of the CIPP model, which include context, input, process and product. The results of the study indicate that the Arpisan Rosakti program is relevant to the needs of schools in facing the era of digital transformations. In terms of input, schools are supported by human resources, School Operational Assistance (BOS) funding, and IT facilities, which are managed in stages. The program implementation process is structured through learning supervision, activity reporting and routine evaluation. In terms of product, the program has a positive impact on improving teachers digital competence and students engagement and creativity. This study presents a comprehensive evaluation of the digital transformation based SBM program in elementary schools using the CIPP model, which has been understudied for a limited time. This model can serve as a practical reference for developing school innovations. These findings demonstrate the effectiveness of the CIPP model in comprehensively assessing and developing programs.